2008
DOI: 10.1002/elps.200700460
|View full text |Cite
|
Sign up to set email alerts
|

Packed‐column capillary electrochromatography and capillary electrochromatography‐mass spectrometry using a lithocholic acid stationary phase

Abstract: The preparation and characterization of a novel lithocholic acid (LCA)-based liquid crystalline (LC) stationary phase (SP) suitable for application in packed-column CEC and CEC coupled to MS is described. The extent of bonding reactions of LCA-SP was assessed using 1 H-NMR, 13 C-NMR and elemental analysis. This characterization is followed by application of the LCA-SP for separation of β-blockers, phenylethylamines (PEAs), polyaromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs). Using the optimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…As illustrated in Fig. 7, six solutes could be separated within 30 min and the mixture was eluted in the order of increasing hydrophobicity on LCCE‐TMOS‐VTMS column with the same order on the liquid crystal stationary phase 35, while all components were co‐eluted with less retention on TMOS‐VTMS column, which indicated that the structure of liquid crystal crown ether played a key role. Compared with supramolecular calixcrown staionary phase 12, more analytes would be separated on LCCE‐TMOS‐VTMS column.…”
Section: Resultsmentioning
confidence: 97%
“…As illustrated in Fig. 7, six solutes could be separated within 30 min and the mixture was eluted in the order of increasing hydrophobicity on LCCE‐TMOS‐VTMS column with the same order on the liquid crystal stationary phase 35, while all components were co‐eluted with less retention on TMOS‐VTMS column, which indicated that the structure of liquid crystal crown ether played a key role. Compared with supramolecular calixcrown staionary phase 12, more analytes would be separated on LCCE‐TMOS‐VTMS column.…”
Section: Resultsmentioning
confidence: 97%